Redes y conjuntos de acción: para aplicaciones estratégicas en los tiempos de la complejidad social - Villasante, Tomás R.; Martín Gutiérrez, Pedro (Política y Sociedad, 2007)
In this article social network analysis (SNA) and some of its techniques are used within the context of a different theoretical proposal from those that are normally applied. We use SNA in participative methodologies, and we try to go beyond the limits of the “how the research is” –merely cognitive– in order to study in a transforming way, “for whom” and “for what” of knowledge. Therefore we do not have a debate about which technique is more accurate in terms of measure, but if it is strategically operative in the transformation of social networks in self-organised and synergic processes. Speech complexity, sociograms, or action set analysis, are less formalized than those in other studies, more precise and descriptive. However, its usefulness –within the processes mentioned above– has to do with the social agents involved, who take part and own the technique, and reflect about their reality, in terms of systems of relationships. Thus, they are able to have conscious strategies en order to transform their own networks. In sum, they show themselves as auto-organized systems.